Haemodynamic studies in high altitude natives with patent ductus arteriosus - Ruiz Carrillo, Luis (1967)
It has been studied by right heart catheterization, 18 natives and residents of height ductus arteriosus. The hemodynamic data were obtained breathing room air and oxygen, being compared with those obtained in 15 patients sea level with the same anomaly, and with data reported for the native healthy height.